Morbidity and mortality profile of preterm neonates admitted in neonatal intensive care unit of a tertiary care centre in Western Uttar Pradesh, India - Hassan, Najia; Mukhopadhyay, Sujaya; Mohan, Sneha (International Journal of Contemporary Pediatrics, 2019)
Background: Preterm birth is a major cause of mortality and morbidity for newborns. Complications of prematurity are becoming more common as more survivors are spending time in Neonatal intensive care unit. Methods: A retrospective hospital based clinical observational study was conducted in NICU in Sharda hospital, a tertiary care centre in Greater Noida. Data regarding neonates′ age, sex, clinical presentation, maternal risk factors, complications and outcome were recorded. Results: A total of 133 preterm neonates were enrolled in the study. Maternal risk factors like Pregnancy induced hypertension (PIH) was seen in 19.5% cases, Urinary tract infection in 15% and Antepartum haemorrhage in 14.2% cases. Among the complications of prematurity, RDS was noted in 38.3% cases, Hyperbilirubinemia in 16.5% and feed intolerance in 15% cases. Sepsis was present in 3% of the preterm. Mortality rate was 7.5%. Most common cause of death was RDS. Conclusions: Pregnancy induced hypertension and Antepartum haemorrhage were important maternal risk factors for prematurity. Respiratory distress syndrome and perinatal asphyxia were the important causes of mortality in the present study.